Psychotic panic and feared sexual assault – 'homosexual panic': the historical role of feared homosexual assault as a contributing factor to self-attack. Issue 2 (2nd July 2016) - Goldblatt, Mark J; Maltsberger, John T
ABSTRACT: Some psychotic patients fall into acute persecutory panic, a subjective experience of helpless terror in the face of anticipated imminent annihilation or dismemberment. These states occur in a wide range of psychotic illnesses and are often associated with command hallucinations and fear of homosexual assault. In a desperate attempt to escape from imaginary enemies, such patients often attack themselves and imagine suicide is survivable. This article addresses the dread of homosexual assault, previously referred to as homosexual panic, and its relationship to patients who attack themselves in a state of desperate psychotic persecution.